Japanese and Finnish teachers' perceptions and self‐efficacy in inclusive education. (27th December 2019) - Yada, Akie; Savolainen, Hannu
Abstract : It has been indicated that teachers' perceptions of the most suitable educational environment for students with different disabilities depends on the type and severity of students' disability. Although the perceptions are found to be different by country, research comparing Japanese teachers' perceptions and perceptions of teachers from other countries is limited. In addition, much less is known about relationships between the perceptions and teachers' self‐efficacy (TSE). This study examines whether teachers' perceptions differ by country (Japan and Finland), severity of disability and disability type. Moreover, the correlations between perceptions and self‐efficacy for inclusive practices are investigated. Quantitative data were collected through a survey from 359 Japanese and 872 Finnish teachers. The first finding on teachers' perceptions is that Finnish teachers' overall perceptions were more inclusive than those of Japanese teachers'. Second, the teachers in both countries preferred segregated environments for students with severe disabilities more than for students with moderate disabilities. Finally, teachers' perceptions were different depending on students' type of disability in both countries. Correlations between teachers' perceptions and self‐efficacy showed that teachers with high self‐efficacy recommended more inclusive placements in both Japan and Finland. However, TSE was correlated only with perceptions of students with moderate disabilities in Japan. These findings mean that even the Japanese teachers with high self‐efficacy thought that students with severe disabilities were better educated in segregated educational settings. The findings are discussed from the viewpoint of sociocultural contexts, which offers useful insights for developing inclusive education.